O psicólogo do CAPS: desafios e impasses na construção de uma identidade - Pereira, Patrícia Omena Costa (2007)
The The CAPS psychologist, challenges and impasses in the construction of an identity theme refers to a theoretical-practical investigation about the psycoanalytic vertex, surrounding the difficulties and challenges faced by psychologists, when attending severe psychotic patients. It is well known that the assistence to madness has been changing in time. It must be considered that the whole process includes advances and also setbacks, being reflection and interlocution with psychoanalisis a useful instrument in building new possibilities of being in this journey. This research is therefore an attempt to raise and map the difficulties, starting from discussion groups, in the light of the psycoanalytic method, building senses to the psychologists experiences when dealing with the primitive areas of mind.